Parents' and Children's Emotion Regulation Strategies in Emotionally Situated Zones: A Cultural-Historical Perspective. Issue 2 (May 2015) - Chen, Feiyan
ALTHOUGH THERE IS A vast amount of literature on emotion regulation strategies, few studies have examined the direct relation between parents' and children's emotion regulation strategies. Those studies, however, are mainly laboratory based. Little attention has been paid to parents' and children's emotion regulation strategies in a naturalistic context. In drawing upon a cultural-historical perspective, this study investigates how parents' and children's emotion regulation strategies are related in everyday family life. A total of 61 hours of video data were collected from four families in Australia. New context-specific emotion regulation strategies and five emotionally situated zones were found. Similarities in emotion regulation strategies used by parents and children were also found. It is argued that children's acquisition of emotion regulation strategies has its origin in parents' everyday use of their own emotion regulation strategies. This study contributes to our understandings of children's development of emotion regulation in the naturalistic contexts of family life. Pedagogical suggestions and future research directions are provided.